Primary and secondary source of energy in the superluminous supernova 2018ibb - Kozyreva, Alexandra; Shingles, Luke; Baklanov, Petr; Mironov, Alexey; Schneider, Fabian (Astronomy and astrophysics, 2024)
We examined a possible pair-instability origin for the superluminous supernova 2018ibb. As the base model, we used a non-rotating stellar model with an initial mass of 250 M⊙ at about 1/15 solar metallicity. We considered three versions of the model as input for radiative transfer simulations done with the STELLA and ARTIS codes: with 25 M⊙ of 56Ni, with 34 M⊙ of 56Ni, and a chemically mixed case with 34 M⊙ of 56Ni. We present light curves and spectra in comparison to the observed data of SN 2018ibb, and conclude that the pair-instability supernova model with 34 M⊙ of 56Ni explains the broadband light curves reasonably well between −100 and 250 days around the peak. Our synthetic spectra have many similarities with the observed spectra. The luminosity excess in the light curves and the blue-flux excess in the spectra can be explained by an additional energy source, which may be an interaction of the supernova ejecta with circumstellar matter. We discuss possible mechanisms that could have caused the circumstellar matter to be ejected in the decades before the pair-instability explosion.